A Novel Synthesis of Substituted Benzo[1,2,4]triazine Derivatives via Copper-Catalyzed Intermolecular N-Arylation of 2-Iodoaniline and Hydrazonoyl Chlorides - Nematpour, Manijeh; Nouri, Reihane (Synlett, 2024)
In this contribution, a speedy and direct approach for the synthesis of benzo[1,2,4]triazine derivatives via a copper-catalyzed intermolecular N-arylation of 2-iodoaniline and hydrazonoyl chlorides is described. The reaction proceeds in THF at room temperature with no need for any ligand. The use of simple and readily available starting materials, mild copper-catalytic reaction conditions, and good yields (72–92%) are remarkable specifications of this protocol.
Keywords: Ullmann coupling; N-arylation; benzo[1,2,4]triazine; copper-catalyzed; hydrazonoyl chlorides; 2-iodoaniline